Taxonomic review of Kokeshia Miyamoto, 1960 from China, with description of ten new species (Hemiptera: Heteroptera: Schizopteridae) - Luo, Jiu-Yang; Xie, Qiang (European Journal of Taxonomy, 2022)
The species of Kokeshia Miyamoto, 1960 from China are reviewed, K. hsiaoi Ren & Zheng, 1992 is redescribed, and ten new species from China are described. Among these new species, K. baii sp. nov., was collected from Hong Kong, and the other nine, K. acutiformis sp. nov., K. bui sp. nov., K. caii sp. nov., K. drepanoides sp. nov., K. hilli sp. nov., K. pengae sp. nov., K. redeii sp. nov., K. renae sp. nov. and K. weirauchae sp. nov., from Yunnan. Thus, the number of known species of this genus is increased from eight to eighteen. Photographs of the habitus, forewing, abdomen and genitalic structures; drawings and scanning electron micrographs of male abdomen and genitalic structures are provided. A key to all the species currently recognized in the genus Kokeshia is presented, a distribution map and checklist for all known species is provided.